(untitled) (Research, Society and Development, 2025)
The research addresses the management of pediatric sepsis in emergency rooms and the importance of implementing evidence-based protocols for early identification and appropriate treatment of this critical condition. The objective was to analyze how the adoption of standardized guidelines influences the reduction of mortality and morbidity rates in children affected by sepsis. The methodology adopted consisted of a qualitative and narrative literature review, with critical analysis of studies, clinical guidelines and relevant scientific articles extracted from qualified academic databases. The main results highlight that the systematic application of protocols, involving early administration of antibiotics, goal-guided volume replacement and continuous monitoring, significantly improves clinical outcomes, reducing mortality and associated complications. In addition, tools such as prognostic scores, triage algorithms and electronic alerts contribute to the rapid recognition of sepsis, while continuous training of health teams is essential for the effectiveness of these interventions. The conclusion indicates that the standardization of pediatric sepsis management, combined with professional training and the use of support technologies, represents an efficient strategy to optimize care in emergency rooms, ensuring a reduction in complications and an improvement in survival rates.